Radio(chemo)therapy in Elderly Patients with Esophageal Cancer: A Feasible Treatment with an Outcome Consistent with Younger Patients - Rochigneux, Philippe; Resbeut, Michel; Rousseau, Frédérique; Bories, Erwan; Raoul, Jean-Luc; Poizat, Flora; Moureau-Zabotto, Laurence (Frontiers in Oncology, 2014)
Background : Although the prevalence of oesophageal cancer increases in elderly patients, its clinical history and outcome after treatment remain poorly described. Methods : Between January 2001 and December 2011, 58 patients (pts) older than 75 years-old received 3D conformal radiotherapy (mean dose 51 Gy) in two French cancer centres. 47/58 (82%) pts received concomitant chemotherapy (with CDDP and/or FU regimens) and 8 pts underwent surgery after primary radiochemotherapy (RCT). Results : Median age was 77.9 years and the performance status was 0 or 1 in 89%. Tumours were mainly adenocarcinoma of lower oesophagus or gastroesophageal junction (n=51, 89%), T3T4 (n=54, 95%) and N1 (n=44, 77%). The mean follow-up was 21.9 months. In the overall population, the median progression free survival was 9.6 months and median overall survival (OS) was 14.5 months. Using univariate analysis, OS was significantly influenced by age (p=0.048), PS (p< 0.001) and surgery (p=0.035). 35 (60.3%) and 18 patients (31%) experienced grade 1-2 or 3-4 toxicity, respectively (CTCAE v4.0). Conclusion : RCT in elderly patients is a feasible treatment and its outcome is close to younger patient’s outcome published in the literature. Surgical resection, after comprehensive geriatric assessment, should be recommended as the standard treatment for adenocarcinoma of lower oesophagus or gastroesophageal junction in elderly patients with good performance status and low comorbidity profile, as it is in younger patients.